Nie-widoki. Fotograficzne narracje o bólu - Michałowska, Marianna (Załącznik Kulturoznawczy, 2018)
The article is based on the analyses of two photo-texts by young Polish photographers, Paweł Starzec and Łukasz Gniadek. Both artists show cultural landscapes in a ‘new topography’ style to tell stories about the war trauma of inhabitants of displayed areas. Makeshift by Starzec is dedicated to victims of the 1992-95 war in Bosnia and Herzegovina and Under the Surface by Gniadek refers to Polish Jews history in Warsaw. Photographers present no visual signs of the bygone tragedy, however – through focusing on landscapes – they direct attention of the viewer to the drama of human loss. Remembering that, according to the title of Susan Sontag’s book, in photography we ‘regard the pain of Others’, I state that a view of pain does not have to be the main means used in visual narration on suffering. Paradoxically, it is a ‘view’ that blocks the empathy for the Other. Thus we need a non-view to understand the experience of those who suffer.